Komunikasi Dan Dakwah Ustadz Yusuf Mansur - Hermansyah Hermansyah; Waluyo Supriadi (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
The purpose of this study was to find a form of communication and propaganda messages Yusuf Mansur. The method used is descriptive qualitative approach. Conclusion The study showed Yusuf Mansur deliver propaganda messages by using persuasive language, and humor with a descriptive introduction Betawi speak Indonesian and Javanese accent. With the approach of the testimony, economics, jurisprudence of worship and shodaqoh. The type of communication is interpersonal communication, propaganda communication, public communication, organizational communication, mass communication, and cross-cultural communication. Propaganda messages in the lecture is divided into three categories, namely, the message aqidah and mua'malah.